2006
DOI: 10.1016/j.jmb.2006.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Histidine Triad-like Motif of the Rotavirus NSP2 Octamer Mediates both RTPase and NTPase Activities

Abstract: SUMMARYRotavirus NSP2 is an abundant nonstructural RNA-binding protein essential for forming the viral factories that support replication of the double-stranded RNA genome. NSP2 exists as stable doughnut-shaped octamers within the infected cell, representing the tail-to-tail interaction of two tetramers. Extending diagonally across the surface of each octamer are four highly basic grooves that function as binding sites for single-stranded RNA. Between the N and C-terminal domains of each monomer is a deep elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…To further understand the RNA-binding characteristics of NSP2, particularly in regard to RNA nucleotides that lack the 5= GG, and to examine whether the C-terminal helix, which contains several basic residues, plays any role in RNA binding, we carried out binding experiments using SPR. Previous studies showed that mutating some of the basic residues that line the groove, particularly residues in the N-terminal domain, diminishes RNA binding (37). Electrostatic potential surface of the NSP2 octamer shows that in addition to a strong electropositive patch close to the cleft, the C-terminal helices of the 2-fold related NSP2 subunits form another strong positively charged patch at either end of the groove (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…To further understand the RNA-binding characteristics of NSP2, particularly in regard to RNA nucleotides that lack the 5= GG, and to examine whether the C-terminal helix, which contains several basic residues, plays any role in RNA binding, we carried out binding experiments using SPR. Previous studies showed that mutating some of the basic residues that line the groove, particularly residues in the N-terminal domain, diminishes RNA binding (37). Electrostatic potential surface of the NSP2 octamer shows that in addition to a strong electropositive patch close to the cleft, the C-terminal helices of the 2-fold related NSP2 subunits form another strong positively charged patch at either end of the groove (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Crystallographic studies of NSP2 with ATP analogs show that nucleoside substrates bind within the cleft, and that ␥-phosphate hydrolysis, involving a phosphohistidine intermediate, is mediated by H225 (14). However, how NSP2 recognizes 5= RNA, which is shown to be a better substrate than NTPs for ␥-phosphate hydrolysis (37), how the narrow catalytic cleft accommodates the 5= nucleotides of RNA, and how, in the context of rotavirus replication, NSP2 makes sequence-specific interactions with conserved 5= GG dinucleotide remain unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These include the NS3 protein of Kunjin virus, which contains signature Walker A and B motifs that play key roles in its RTPase activities (26), and the rotavirus NSP2 protein which employs a histidine triad for ␥ phosphate hydrolysis (41). Inspection of the VSV L protein sequence indicates that the sequence lacks any such motifs.…”
Section: Discussionmentioning
confidence: 99%